PENGARUH CORPORATE GOVERNANCE, KEPEMILIKAN KELUARGA, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN (FIRM SIZE) TERHADAP BIAYA UTANG - Vhika Meiriasari (Jurnal Ilmiah Ekonomi Global Masa Kini)
The objective of this study was to analyze the effects of corporate governance, family ownership, institutional ownership and the size of the company on the cost of debt. The samples used in this study were 12 companies listed in the Indonesia Stock Exchange (IDX), which participated in the program of Corporate Governance Perception Index (CGPI), which was organized by the Institute of Indonesian Corporate Governance (IICG) for five consecutive years in the period of 2008 - 2012. The technique of analysis used in this study was the multiple linear regression method.In this study, the cost of debt was calculated on the basis of the amount of interest expense paid by the companies within one year divided by the average amount of loans that generated such interest (interest bearing debt). The corporate governance was measured by using the score of CGPI (Corporate Governance Perception Index), the size of the company (firm size) was measured by means the natural logarithm of the total assets of the companies. Whereas the family ownership and institutional ownership was measured by using dummy variables with the criteria of 1 for the number of the shares ownership (family ownership or institutional ownership) of above 20% or more and that of 0 for the shares ownership (family ownership or institutional ownership) of less than 20%. The results of the study showed that corporate governance, family ownership, institutional ownership and the size of the company (firm size) simultaneously affected the cost of debt.Key words : Corporate Governance, Family Ownership, Institutional Ownership, Company Size (Firm Size), Cost of                     Debt